Epidemiological Profile of Burn Cases among autopsies Conducted in Dept. of FMT, RIMS, Ranchi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction : Every year, it was found that burns caused by fire were responsible for about 265,000 deathsglobally. More than 90% of fatal fire-related burns occur in developing or lower and middle income countries(LMICs). Out of this, South- East Asia alone accounts for more than half of these fire-related deaths. InSouth East Asian region, death due to Burns in girl / women is more than that of Tuberculosis, HIV/AIDSand malaria combined. In India, burn injury is found to be one of the major causes of death, especially infemales. The problem of death due to burns in developing countries like India is primarily due to varioussocio-cultural factors prevalent in the country. Some of these factors include poor housing conditions, poormaintenance of electrical appliances, and customs of wearing dresses like sarees or dupatta, practice ofdowry, illiteracy level and poverty.Material and Method: Materials for the present study were collected from the medico legal autopsies of296 burn cases, performed at the mortuary of Rajendra Institute of Medical Sciences (RIMS), Ranchi, duringthe period from January 2018 to December 2018. A detailed performa was designed with a definite set ofquestionnaire which formed the basis of this study.Results: In our study, out of the 296 cases, the most common age group involved was 21-30 years with afemale sex predilection (female to male ratio of 1.5:1). As far as the marital status is concerned, most caseswere of married men and women (66.22%) involving mostly Housewives (43.25%). The most common timeperiod involved was between 4 PM to 10 PM (35.47%). Most of the cases took place at home (75.34%).Conclusion:- Our study primarily focuses on the epidemiological profile of data involving burn cases in thispart of India which is relatively a backward area comprising of a majority of tribal population.